2006
DOI: 10.1128/cvi.00122-06
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcal Type II and III Conjugate Vaccines: Physicochemical Properties That Influence Immunogenicity

Abstract: Recent efforts toward developing vaccines against group B streptococci (GBS) have focused on increasing the immunogenicity of GBS polysaccharides by conjugation to carrier proteins. However, partial depolymerization of GBS polysaccharides for the production of vaccines is a difficult task because of their acid-labile, antigenically critical sialic acids. Here we report a method for the partial depolymerization of type II and III polysaccharides by mild deaminative cleavage to antigenic fragments with reducing-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…genicity may arise from the higher percentage of total CPS in the 2:1 than in the 1:1 mixed conjugate, which might influence the capacity of the conjugate to modulate the immune cells, including antigen-presenting cells (APCs), presumably through its higher molecular mass/size, which might ease uptake and internalization. In this regard, it has been shown that the polysaccharide size used for conjugation, the obtained conjugate size, and the degree of polysaccharide-protein cross-linking influence the immunogenicity and protective efficacy of a GBS type III-TT conjugate vaccine (74,77,78). Further studies evaluating how the aforementioned parameters affect the immunogenicity of an S. suis type 2 CPS conjugate, which can contribute to improvements of the design of the conjugate vaccine, are under way.…”
Section: Figmentioning
confidence: 99%
“…genicity may arise from the higher percentage of total CPS in the 2:1 than in the 1:1 mixed conjugate, which might influence the capacity of the conjugate to modulate the immune cells, including antigen-presenting cells (APCs), presumably through its higher molecular mass/size, which might ease uptake and internalization. In this regard, it has been shown that the polysaccharide size used for conjugation, the obtained conjugate size, and the degree of polysaccharide-protein cross-linking influence the immunogenicity and protective efficacy of a GBS type III-TT conjugate vaccine (74,77,78). Further studies evaluating how the aforementioned parameters affect the immunogenicity of an S. suis type 2 CPS conjugate, which can contribute to improvements of the design of the conjugate vaccine, are under way.…”
Section: Figmentioning
confidence: 99%
“…PLDpolysaccharide conjugate vaccines were prepared from CPS serotypes 6B, 14, 19F and 23F by reductive amination and TT-polysaccharide conjugate vaccines were similarly prepared and used for comparison. The PLD conjugates were generally equivalent to or better than the TT conjugates in CPS-specific responses (Michon et al, 1998). The pneumococcal toxin pneumolysin is an important pneumococcal virulence factor, which appears to satisfy the necessary criteria for use in vaccines.…”
Section: Pneumolysin-polysaccharide Capsular Conjugate Vaccinesmentioning
confidence: 94%
“…A genetically detoxified pneumolysin, pneumolysoid (PLD) was investigated as a carrier protein for pneumococcal capsular polysaccharide (CPS). Such a CPS-PLD conjugate might provide additional protection against pneumococcal infections and result in tissue damage (Michon et al, 1998) Ply is a potent hemolytic cytotoxin, which can be produced by all essential strains of S. pneumoniae isolated clinically. Its status as an important virulence protein has been confirmed by previous demonstration that genetically defined Ply-negative mutant pneumococcus strains have significantly reduced virulence (Paton et al, 1991).…”
Section: Pneumolysin-polysaccharide Capsular Conjugate Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the collection of the unbound effluent from each of the columns, bound antibodies were eluted with 3.0 M KSCN. Fractions collected from the columns were analyzed by ELISA (18). Representative ELISAs of column profiles eluted with 3.0 M KSCN following loading are shown in Fig.…”
mentioning
confidence: 99%